About illegal trafficking as an extra sign of the corpus delicti provided for in the art. 228 of the Criminal Code of the Russian Federation - Norvartyan, Yury S. (Journal of the Belarusian State University. Law, 2021)
This article focuses on two alternative actions under the art. 228 of the Criminal Code of the Russian Federation, which are illegal possession and illegal trafficking. Based on the materials of modern law enforcement practice, it is confirmed that a person’s presence of narcotic drugs, psychotropic substances or their analogues for personal consumption is not an illegal trafficking and is covered by the sign of their illegal possession. The conclusion that illegal trafficking is effectively criminalised is justified only when it is aimed at marketing.